Transforming science literacy: assessing the ability of chemistry teacher candidates through the viewpoint of Islamic values - Wahyuni, Tutik Sri; Silfianah, Ifah (Psychology, Evaluation, and Technology in Educational Research, 2024)
Science literacy assessment is important to familiarize students with literacy questions based on aspects of science knowledge and its interaction with the environment, technology, and society. Students' low science literacy is often caused by teachers' low science literacy. This study aims to analyze (1) the science literacy skills of chemistry education students in basic chemistry courses; and (2) the science literacy skills of chemistry education students based on competency aspects which are divided into three achievement indicators. This research is a descriptive study with a quantitative approach, with subjects 21 semester 6 students of the chemistry education study program at UIN Sayyid Ali Rahmatullah Tulungagung. The instrument used was a scientific literacy test in the form of an essay test with 22 questions which have been validated by 2 chemistry education lecturers, and the test results with a test reliability of 0.629, as well as a difficulty level of 1 easy question, 19 medium, and 2 difficult. The results showed that (1) students' science literacy skills were in the "sufficient" category with an average score of 43.9. (2) Analysis based on competency aspects shows the ability to explain phenomena scientifically and identify scientific issues is in the sufficient category, but the use of scientific evidence is low. The findings are expected to provide input to improve learning and practice of science literacy in preparing students as future educators.